Mycolactone as Analgesic: Subcutaneous Bioavailability Parameters - Babonneau, Jérémie; Bréard, Dimitri; Reynaert, Marie-Line; Marion, Estelle; Guilet, David; Saint André, Jean-Paul; Croué, Anne; Brodin, Priscille; Richomme, Pascal; Marsollier, Laurent (Frontiers in Pharmacology, 2019)
Mycobacterium ulcerans is the bacillus responsible for Buruli ulcer, an infectious disease and the third most important mycobacterial disease worldwide, after tuberculosis and leprosy. M. ulcerans infection is a type of panniculitis beginning mostly with a nodule or an edema, which can progress to large ulcerative lesions. The lesions are caused by mycolactone, the polyketide toxin of M. ulcerans. Mycolactone plays a central role for host colonization: it provokes an immunomodulatory effect and an analgesic effect. Mycolactone induces analgesia by targeting type-2 angiotensin II receptors (AT2R), causing cellular hyperpolarization. Moreover, a single subcutaneous injection of mycolactone into the mouse footpad can induce long-lasting hypoesthesia, with significant effects for one to two days. It has been suggested that the long-lasting hypoesthesia results from the persistence of a significant amount of mycolactone locally, long after the injection, probably due to its slow elimination from tissues. Based on this hypothesis, for the first time, we investigated the correlation between hypoesthesia and mycolactone bioavailability in the tissue. Various quantities of mycolactone were injected in mouse tissue and hypoesthesia was recorded, over a period of 48 h, with nociception assays. The hypoesthesia effect was maximal 6 hours after the injection of 4 µg mycolactone. The return to the basal state 48 h after injection demonstrates the absence of nerve damage. Surprisingly, we have shown that mycolactone levels decreased strongly during the first hours (70% have been eliminated after 4 h, 90% after 10 h) but the small amount remaining was sufficient to induce hypoesthesia during 24h. Our results demonstrated that mycolactone is rapidly eliminated but very small amounts of mycolactone were sufficient to induce a local biological effect. These results suggest that mycolactone, bound to AT2R, is protected against elimination. On the other hand, our data showed that systemic diffusion of mycolactone in the context of infection is unlikely. To conclude our study underlines that mycolactone could be considered as promising analgesic.